Modifying a clinical linear accelerator for delivery of ultra-high dose rate irradiation. (October 2019) - Lempart, Michael; Blad, Börje; Adrian, Gabriel; Bäck, Sven; Knöös, Tommy; Ceberg, Crister; Petersson, Kristoffer
Highlights: We show how to modify a clinical linear accelerator to produce ultra-high dose rates, high enough for FLASH irradiation. The FLASH delivery is controlled with a microcontroller on an electron pulse level. A FLASH irradiation dose rate is reached at the cross-hair, MLC, and wedge position, with ≥30, ≥80, and ≥300 Gy/s, respectively. Removal of the scattering foils results in an increased output of ≥120, ≥250, and ≥1000 Gy/s, at the three positions. Abstract: Objectives: The purpose of this study was to modify a clinical linear accelerator, making it capable of electron beam ultra-high dose rate (FLASH) irradiation. Modifications had to be quick, reversible, and without interfering with clinical treatments. Methods: Performed modifications: (1) reduced distance with three setup positions, (2) adjusted/optimized gun current, modulator charge rate and beam steering values for a high dose rate, (3) delivery was controlled with a microcontroller on an electron pulse level, and (4) moving the primary and/or secondary scattering foils from the beam path. Results: The variation in dose for a five-pulse delivery was measured to be 1% (using a diode, 4% using film) during 10 minutes after a warm-up procedure, later increasing to 7% (11% using film). A FLASH irradiation dose rate was reached at the cross-hair foil, MLC, and wedge position, with ≥30, ≥80, and ≥300 Gy/s, respectively. Moving the scattering foils resulted in an increased output of ≥120, ≥250, and ≥1000 Gy/s, at the three positions. The beam flatness was 5% at the cross-hair position for a 20 × 20 and a 10 × 10 cm 2 area, with and without both scattering foils in the beam. The beam flatness was 10% at the wedge position for a 6 and 2.5 cm diametric area, with and without the scattering foils in the beam path. Conclusions: A clinical accelerator was modified to produce ultra-high dose rates, high enough for FLASH irradiation. Future work aims to fine-tune the dose delivery, using the on-board transmission chamber signal and adjusting the dose-per-pulse.